PENGARUH KEPUASAN KERJA, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP TURNOVER INTENTION KARYAWAN LAKSANA BARU SWALAYAN MAJENANG - Fauzan Ozan Haidar; Hengky Widhiandono; Suyoto Suyoto; Alfalisyado Alfalisyado (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study purposes to examine the impact of job satisfaction, work motivation, and work discipline on employee turnover intention at Laksana Baru Swalayan Majenang. This investigation method is quantitative to test the relationship between variables. The population in this investigation was 89 employees of Laksana Baru Swalayan Majenang. The sampling technique uses a census. The data collection instrument utilized a five-level Likert scale questionnaire. The analysis tool uses SEM PLS. The findings of the research found that job satisfaction had a negative impact on turnover intention, work motivation had a negative impact on turnover intention, and work discipline had a negative impact on turnover intention. This study purposes to examine the impact of job satisfaction, work motivation, and work discipline on employee turnover intention at Laksana Baru Swalayan Majenang. This investigation method is quantitative to test the relationship between variables. The population in this investigation was 89 employees of Laksana Baru Swalayan Majenang. The sampling technique uses a census. The data collection instrument utilized a five-level Likert scale questionnaire. The analysis tool uses SEM PLS. The findings of the research found that job satisfaction had a negative impact on turnover intention, work motivation had a negative impact on turnover intention, and work discipline had a negative impact on turnover intention.